2006
DOI: 10.1002/cbic.200500284
|View full text |Cite
|
Sign up to set email alerts
|

Guanine Oxidation by Electron Transfer: One‐ versus Two‐Electron Oxidation Mechanism

Abstract: The degeneracy of the guanine radical cation, which is formed in DNA by oxidation of guanine by electron transfer, was studied by a detailed analysis of the oxidation products of guanine on oligonucleotide duplexes and by labeling experiments. It was shown that imidazolone, the major product of guanine oxidation, is formed through a one-electron oxidation process and incorporates one oxygen atom from O2. The formation of 8-oxo-7,8-dihydroguanine by a two-electron oxidation process was a minor pathway. The two-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 64 publications
0
38
0
Order By: Relevance
“…It was suggested that the compound arises from hydroxylation at C5 of a (G-H) + intermediate, leading to an unstable compound with one labeled oxygen atom from H 2 18 O added at C5. This intermediate was expected to rearrange at physiological pH into an Sp-like structure (Scheme 3) that would be sensitive to hydrolytic ring opening [62]. The Rokita laboratory also found the mass of G+34 as the major product of DNA oxidation with a dinuclear copper complex, [Cu 2 II (PD′O)(H 2 O) 2 ] 3+ where PD′OH is a pyridylalkylamine containing binucleating ligand [63].…”
Section: Introductionmentioning
confidence: 99%
“…It was suggested that the compound arises from hydroxylation at C5 of a (G-H) + intermediate, leading to an unstable compound with one labeled oxygen atom from H 2 18 O added at C5. This intermediate was expected to rearrange at physiological pH into an Sp-like structure (Scheme 3) that would be sensitive to hydrolytic ring opening [62]. The Rokita laboratory also found the mass of G+34 as the major product of DNA oxidation with a dinuclear copper complex, [Cu 2 II (PD′O)(H 2 O) 2 ] 3+ where PD′OH is a pyridylalkylamine containing binucleating ligand [63].…”
Section: Introductionmentioning
confidence: 99%
“…This method is highly sensitive and has previously allowed us to detect about 1 % of oxidative DNA damage. [39,40] Under these experimental conditions the short ODN was single-stranded.…”
Section: Resultsmentioning
confidence: 99%
“…The retention times and the mass data of oxidized ODN were known from previous work on 5'-CAGCTG. [39,40] Formation of an oxidized oligonucleotide strand (even 1 % yield, 0.1 mm) would have been detected by the method of analysis. The yield of www.chemeurj.org spontaneous reduction determines the subsequent concentration of diffusible oxidative species from the released axial ligands (HOCl or Cl 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…The retention times and the mass data of oxidized ODN were known from previous work on 5′‐CAGCTG 39. 40 Formation of an oxidized oligonucleotide strand (even 1 % yield, 0.1 μ M ) would have been detected by the method of analysis. The yield of spontaneous reduction determines the subsequent concentration of diffusible oxidative species from the released axial ligands (HOCl or Cl 2 ).…”
Section: Discussionmentioning
confidence: 99%